Effect of Selected Combined Training Program on leptin serum levels of men with multiple sclerosis - منیره مسعودی نژاد; حسین شیروانی (Shahid Beheshti University, 2011)
The purpose of this study was to determine the effect of eight weeks combined training on leptin serumlevels in men with multiple sclerosis (MS). Twenty men with MS age 34.45±3.75 yrs, mean ExpandedDisability Status Scale 1.80±0.65, weight 71.95±7.45 Kg and body mass index 24.78±2.01 Kg/m2, wererandomly divided to subgroup, experimental (n=10) and control (n=10) groups. The experimental group,beside consuming the prescribed drugs, participated in eight weeks combined training (include warmingfor 20 minutes, aerobic training for 15 minutes with 50-60% maximum heart rate strength exercises withupper and lower extremities for 15 minutes with 50-70% 1RM and recovery for 10 minutes) 3 times aweek for 60 minutes, while control group only consumed prescribed drugs. In each group two restingblood samples were taken before and after training. The data were analyzed with t-student method withsignificant level at (P<0.05). The result of this study showed that serum leptin levels in experimentalgroup were significantly decreased (P<0.0001), But increased in control group did not significantlyincreased (P<0.75). However, the result suggests that combined training program can decrease serumleptin levels in men with multiple sclerosis.